Chimeric green fluorescent protein-aequorin as bioluminescent Ca(2+) reporters at the single-cell level - Baubet, Valérie (The National Academy of Sciences, 2000)
Monitoring calcium fluxes in real time could help to understand the development, the plasticity, and the functioning of the central nervous system. In jellyfish, the chemiluminescent calcium binding aequorin protein is associated with the green fluorescent protein and a green bioluminescent signal is emitted upon Ca(2+) stimulation. We decided to use this chemiluminescence resonance energy transfer between the two molecules. Calcium-sensitive bioluminescent reporter genes have been constructed by fusing green fluorescent protein and aequorin, resulting in much more light being emitted. Chemiluminescent and fluorescent activities of these fusion proteins have been assessed in mammalian cells. Cytosolic Ca(2+) increases were imaged at the single-cell level with a cooled intensified charge-coupled device camera. This bifunctional reporter gene should allow the investigation of calcium activities in neuronal networks and in specific subcellular compartments in transgenic animals.